Comparative study of dermatoglyphic patterns in identical twins - R Anita Gune; Satish Patki; J Anand Pote (Wolters Kluwer Medknow Publications, 2017)
Background and aims: Dermatoglyphics has been studied extensively in chromosomal disorders and also in various diseases. Identical twins cannot be distinguished based on DNA. It is claimed that identical twins can be distinguished based on their finger prints, retina, and thermogram and iris patterns. It will be really interesting to know whether the identical twins have same dermatoglyphic patterns or not. Materials and Methods: 24 pairs of identical twins were examined for quantitative and qualitative similarities of finger print patterns; patterns on the palm, 'atd'angle, 'a-b'ridge count and palmar creases. Finger prints were evaluated for loop, arch, whorl and the data was recorded. Paired sample correlation test was applied to analyse 'a-b'ridge count and 'atd' angle. Results: We have found that on comparison of finger tip patterns there are differences of about 33.33%. 'a- b'ridge count in cases studied showed mean range from 38.23 to 38.37 on right and left hands respectively. This indicates there is close similarity in the 'a-b'ridge count of identical twins, 'atd' angle showed close similarity in mean ranging from 46.23 to 46.10 on right and left hand respectively. Conclusion: Finger tip patterns is superior parameter to differentiate Identical twins compared to 'a-b'ridge count and 'atd' angle.